2019
DOI: 10.1007/s00520-019-04764-7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring health-related quality of life in colorectal cancer patients: systematic review of measurement properties of the EORTC QLQ-CR29

Abstract: Introduction The EORTC QLQ-CR29 is a patient-reported outcome measure to evaluate health-related quality of life among colorectal cancer patients in research and clinical practice. The aim of this systematic review was to investigate whether the initial positive results regarding the measurement properties of the QLQ-CR29 are confirmed in subsequent studies. Methods A systematic search of Embase, Medline, PsycINFO, and Web of Science was conducted to identify studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Second, while discussion on the methodology used was limited given the small number of studies available, we noted the lack of quantitative scales specifically validated for CRC patients. Only one scale used the EORTC QLQ‐CR29 36 which measures QOL domains characteristic to CRC. The inclusion of cancer‐specific scales is essential in uncovering psychosocial experiences unique to CRC, such as the influence of stoma, sexual dysfunction, and embarrassment with bowel movements.…”
Section: Discussionmentioning
confidence: 99%
“…Second, while discussion on the methodology used was limited given the small number of studies available, we noted the lack of quantitative scales specifically validated for CRC patients. Only one scale used the EORTC QLQ‐CR29 36 which measures QOL domains characteristic to CRC. The inclusion of cancer‐specific scales is essential in uncovering psychosocial experiences unique to CRC, such as the influence of stoma, sexual dysfunction, and embarrassment with bowel movements.…”
Section: Discussionmentioning
confidence: 99%
“…Scores are transformed linearly, giving a score between zero and 100. The results of our study were compared to the results of other studies that showed that the higher the scores, the better they function on the functioning scales and a higher level of symptoms on the symptoms scale [27].…”
Section: Discussionmentioning
confidence: 85%
“…For this second search, a sensitive PubMed search filter developed by Terwee et al [ 37 ] was applied. Translations of this filter for the remaining databases were taken from the COSMIN website and from other published COSMIN reviews [ 38 , 39 ] with permission from the authors. Both searches were conducted until March 2021 without restriction regarding the time of publication (databases were searched from inception).…”
Section: Methodsmentioning
confidence: 99%